Personality and Public Sector Employment - Terhi Maczulskij; Jutta Viinikainen (Institute of Labor Economics (IZA), 2021)
Using a representative survey combined with register data on long-term labour market outcomes, this paper examines how personality traits predict sorting into public and private sector employment among prime working-age individuals. To gain deeper insights into the dynamic dimensions of the sorting process, we also study the role of personality traits in the decisions to enter or exit public sector work. Our robust results show that public sector workers are more social, while private sector workers exhibit more orderly behaviour. The link between orderliness and sectoral sorting is partly explained by the reduced entry of individuals with high levels of orderliness into public sector employment. High sociability is also financially better rewarded in the public sector, which may implicitly indicate a good fit between this trait and job performance in that sector.
Keywords: J23; J45; 330; personality; public sector; private sector; occupational choice